(untitled) (Jurnal EurekaMatika, 2021)
Blood flows every second throughout the body. Blood flow carries substances needed for the activity of body organs, such as oxygen and other nutrients. Blood flow that occurs as a result of changes in blood pressure periodically causes the velocity of blood flow to change at any time. The purpose of this study is to construct a mathematical model for blood-flow velocity with periodic gradient pressure. The model is derived from the Navier Stokes equation and continuity equations in polar cylindrical coordinates. A solution of the model is obtained by the variable separation method. Based on the model, the velocity profile of the blood flow is obtained. The factors that influence it are the radius of the blood vessel, the amplitude of the blood pressure gradient, frequency gradients of blood pressure and kinematic viscosity of blood. ABSTRAK Darah mengalir setiap detik di dalam seluruh tubuh. Aliran darah yang membawa zat-zat yang diperlukan untuk aktivitas organorgan tubuh, seperti oksigen dan zat-zat nutrisi lainnya. Aliran darah yang terjadi akibat dari perubahan tekanan darah secara periodik menyebabkan kecepatan aliran darah berubah-ubah di setiap waktu. Tujuan penelitian ini membuat model matematika untuk kecepatan aliran darah dengan tekanan yang berubah. Model tersebut dibangun dari persamaan Navier Stokes untuk kecepatan aliran fluida satu arah dengan koordinat polar silinder dan persamaan kontinuitas. Pencarian solusi analitik dari model dilakukan dengan metode pemisahan variable. Berdasarkan model tersebut diperoleh profil kecepatan alirah darah dan faktor-faktor yang mempengaruhinya yaitu jari-jari pembuluh darah, amplitudo gradien tekanan darah, frekuensi gradien tekanan darah dan viskositas kinematik darah.